2016
DOI: 10.5507/bp.2015.045
|View full text |Cite
|
Sign up to set email alerts
|

Serum carboxymethyl-lysine, a dominant advanced glycation end product, is increased in women with gestational diabetes mellitus

Abstract: Aims. The objective of the study was to measure one of the circulating Advanced Glycation End Products (AGEs) -Nε-(carboxymethyl)lysine (CML) -in a case-control study (n = 307) of pregnant women with gestational diabetes mellitus (GDM) and physiological pregnancies and to ascertain the factors contributing to CML levels and the potential relevance of CML for selected perinatal and postpartum outcomes. Methods. All subjects underwent oGTT between 24 th and 30 th week of gestation and GDM was diagnosed according… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…Regarding the geographical distribution, the review included seven studies from Europe [30][31][32][33][34][35][36], seven studies from Asia [37][38][39][40][41][42][43] and two studies from Latin America [44,45]. Thirteen of these studies employed case-control design [30,32,33,[35][36][37][38][39][40][41][42][43][44] whereas the rest three studies were cross-sectional in design [31,34,45]. Specifically, the meta-analysis of AGEs involved 774 cases and 834 controls.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the geographical distribution, the review included seven studies from Europe [30][31][32][33][34][35][36], seven studies from Asia [37][38][39][40][41][42][43] and two studies from Latin America [44,45]. Thirteen of these studies employed case-control design [30,32,33,[35][36][37][38][39][40][41][42][43][44] whereas the rest three studies were cross-sectional in design [31,34,45]. Specifically, the meta-analysis of AGEs involved 774 cases and 834 controls.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The systematic review and meta-analysis involved studies that reported the outcome measures at both first and second trimesters [32], first and third trimesters [36], second trimester [30,31,34,41,44], second and third trimesters [38,42], and third trimester of pregnancy [33,35,37,39,40] whereas two studies did not specify gestational period during sample collection [43,45]. Blood sample was collected from 13 studies [30,31,33,[35][36][37][38][39][40][42][43][44][45], skin sample from two studies [32,34], and placenta sample from one study [41] ( Table 1). For analysis of specific AGEs and metabolic biomarkers, five and four studies were included to generate the pooled estimates of HOMA-IR [31,37,42,43,45], and HbA1c [31,33,37,43], respectively.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…in addition, other studies have identified that insulin therapy does not improve fetal or newborn metabolic outcomes (8), and that it can cause alterations in the placenta (9), indicating factors other than glucose may be involved in the pathophysiology of GdM. in a number of studies, advanced glycation end products (AGEs) have been identified to be present in higher levels in women suffering from GdM (10,11) and these products are associated with poor fetal outcomes (12). aGes are reportedly involved in increasing the permeability of retinal vascular and endothelial cells (13,14).…”
Section: Low Molecular Weight Heparin (Nadroparin) Improves Placentalmentioning
confidence: 99%
“…Results -including our earlier study of carboxymethyl lysine in GDM pregnancy and postpartumshowed mostly increased AGEs plasma levels in GDM compared to healthy pregnant women [9][10][11][12]. Formation of AGEs may be limited by the action of Bprotective^pathways that either metabolize existing precursors of AGEs (e.g.…”
Section: Introductionmentioning
confidence: 96%